2019
DOI: 10.1097/mrr.0000000000000314
|View full text |Cite
|
Sign up to set email alerts
|

Turkish adaptation of Parkinson fatigue scale and investigating its psychometric properties

Abstract: Parkinson’s disease (PD) is one of the most common chronic degenerative diseases of the nervous system. In PD, nonmotor symptoms are seen as frequently as motor symptoms. Fatigue can occur in all stages of PD and leads to significant disabilities. The aim of this study was to investigate the psychometric properties of the Turkish version of Parkinson fatigue scale (PFS). Ninety-six patients with idiopathic PD were included in this study with a cross-sectional and test–retest design. Structural validity, intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
4
1
0
Order By: Relevance
“…In agreement with the confirmatory analysis of previous studies,18,22,23 our exploratory factor analysis showed results compatible with the unidimensional nature of the PFS-16, including the amount of variance explained (67% vs 64%).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In agreement with the confirmatory analysis of previous studies,18,22,23 our exploratory factor analysis showed results compatible with the unidimensional nature of the PFS-16, including the amount of variance explained (67% vs 64%).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, as measured by Cronbach’s alpha, the internal consistency for the scale in our study (0.93) was in line with those found in previous studies 1824. Similarly, corrected item-total correlations (Table 4) overlap previous findings 2023. Item homogeneity (r S =0.19) was found to satisfy the accepted value of ≥0.15, indicating sufficient association among the items 19,22.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, the individuals reported the dose of levodopa levels and many of them use other antiparkinsonian medicine associated. Other studies also confirmed the association of the presence or severity of fatigue (HY) and LEDD 35,36,37 .…”
Section: Discussionmentioning
confidence: 63%